Aging resistance of infiltrated monolithic zirconia compared to noninfiltrated monolithic zirconia: A systematic review of in vitro studies - Aditi Aneesh Kanitkar; Paresh Gandhi; Aneesh Kanitkar; S Vishnu Priya; Sujatha Paranna; Seema Patil (Wolters Kluwer Medknow Publications, 2022)
Aim: The aim of the study is to systematically assess the impact of low-temperature degradation (LTD) simulation in an autoclave on mechanical and microstructural properties of infiltrated monolithic zirconia compared to the noninfiltrated zirconia. Settings and Design: Systematic review following Preferred Reporting Items for Systematic Reviews and Meta-Analysis 2020 guidelines. Materials and Methods: An electronic search was done within these databases: PubMed, Scopus, and Web of Science, Science Direct, Embase, Wiley, Google Scholar for articles published between 2000 and March 2021. Search results that met eligibility criteria were categorized into two groups based on properties assessed of infiltrated monolithic zirconia exposed to LTD (also called aging simulation) - (a) mechanical (flexural strength and fracture toughness) and (b) microstructural properties (phase transformation rate and m content). Statistical Analysis Used: Qualitative analysis. Results: The search identified 272 preliminary results. After discarding duplicates, and screening of titles, abstracts, and full texts, 10 articles finally met inclusion criteria. Data were collected on author's details and their countries, journal and year of publication, type and percentage of infiltration, aging protocol (duration and temperature), mechanical, and microstructural properties. All the included studies invariably revealed better aging resistance without a change in mechanical properties for infiltrated monolithic zirconia as compared to noninfiltrated species. Conclusion: Infiltration within monolithic zirconia can reduce degradation and simultaneously maintain their mechanical properties by preventing water entry into grain contours. The final m content was less for infiltrated Zirconium, indicating a lesser phase transformation and better aging resistance. Other Information: Systematic review protocol registered at PROSPERO CRD42021248153.